SmartCloud QR: a next-gen online attendance system leveraging QR code and cloud technology - Kriangsak Chanthinok; Palan Jantarajaturapath; Konkanok Donsophon (Institute of Advanced Engineering and Science, 2026)
This study presents SmartCloud quick response (QR), a cloud-based attendance monitoring system designed to enhance efficiency, accuracy, and fraud prevention in educational institutions. Traditional paper-based attendance methods are time-consuming, error-prone, and vulnerable to proxy attendance. To address these limitations, the system was developed using a software-as-a-service architecture that integrates QR code technology with cloud computing, enabling scalable deployment without requiring dedicated institutional hardware infrastructure. The research was conducted in two phases: phase 1 involved user needs analysis to identify operational challenges in attendance management and phase 2 evaluated system effectiveness through large-scale implementation involving 27,070 participants. Statistical analyses, including independent samples t-tests and one-way analysis of variance (ANOVA), were performed to examine satisfaction differences across gender and user roles. The results demonstrated a high overall satisfaction rate (92.84%), with only minimal and practically negligible differences observed across demographic groups. The findings empirically support the technology acceptance model (TAM), indicating that perceived usefulness and ease of use are reinforced by fraud prevention mechanisms and infrastructure-light deployment. This study contributes to the applied educational informatics literature by introducing a scalable software-as-a-service attendance framework that enhances fraud prevention, reduces institutional hardware investment, and operationalizes privacy-by-design principles in large-scale real-world implementation.